Análise termodinâmica e performance de uma bancada de refrigeração por absorção contínua de amônia - Ferreira Junior, Rodney (2014)
The subject on this work aims to cooling by continuous absorption of ammonia applied to a bank located in the didactic laboratory energies of UTFPR - Campus: Cornelius, where the main cooling methods have been reported, also with understanding the functioning of the bench and its components. Were put in place for three different types of heating thermodynamic analysis for the cooling system of the generator, namely: electrical resistance using the power source coming from the power supply, use of photovoltaic panels for energy generation and transmission for strength and LPG gas as a heat supplier for the system, through flame. With the cycle analyzes the calculation of the gas LPG operating performance was more efficient compared to the electricity network and photovoltaic panels, and its superior efficacy to 4% and 5% respectively.